Spin-controlled generation of indistinguishable and distinguishable photons from silicon vacancy centres in silicon carbide - Morioka, Naoya; Babin, Charles; Nagy, Roland; Gediz, Izel; Hesselmeier, Erik; Liu, Di; Joliffe, Matthew; Niethammer, Matthias; Dasari, Durga; Vorobyov, Vadim; Kolesov, Roman; Stoehr, Rainer; et al. (Nature Communications, 2020)
Quantum systems combining indistinguishable photon generation and spin-based quantum information processing are essential for remote quantum applications and networking. However, identification of suitable systems in scalable platforms remains a challenge. Here, we investigate the silicon vacancy centre in silicon carbide and demonstrate controlled emission of indistinguishable and distinguishable photons via coherent spin manipulation. Using strong off-resonant excitation and collecting zero-phonon line photons, we show a two-photon interference contrast close to 90% in Hong-Ou-Mandel type experiments. Further, we exploit the system’s intimate spin-photon relation to spin-control the colour and indistinguishability of consecutively emitted photons. Our results provide a deep insight into the system’s spin-phonon-photon physics and underline the potential of the industrially compatible silicon carbide platform for measurement-based entanglement distribution and photonic cluster state generation. Additional coupling to quantum registers based on individual nuclear spins would further allow for high-level network-relevant quantum information processing, such as error correction and entanglement purification.
CRIS-Team Scopus Importer:2020-10-30